Karakterisasi Pengaruh Temperatur Kalsinasi pada Intensitas emisi Material Luminisensi ZnO:Zn: Diky Anggoro, Raidah Syarifah, Hasto Sunarno, F Faridawati, Bachtera Indarto - Diky Anggoro Diky Anggoro; Raidah Syarifah Raidah Syarifah; Hasto Sunarno Hasto Sunarno; Faridawati Faridawati; Bachtera Indarto Bachtera Indarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
Characterization of the effect of temperature on emission intensity ZnO:Zn luminance material has been carried out. This research was conducted to determine the optical properties of ZnO:Zn as a luminous material and the effect of temperature on emission intensity of ZnO luminance material will be analyzed: Zn at 5% dopant concentration. ZnO synthesis was carried out using the solution phase method and in obtaining the ZnO:ZnO:luminous material, the milling method was used. The best absorbance spectrum is produced by ZnO:Zn with the highest calcination temperature of 4000 C. Based on the photoluminniscence spectrum characterization it is known that ZnO: Zn luminance material with temperature variations is capable of emitting green light with a wavelength range of 523 nm. Temperature variation given will affect the high intensity of ZnO emission: Zn produced as the temperature increases.